Variants in the Imprinted IGF2 Gene: A Review and Phasing of De Novo Variants Using Long‐Read Sequencing - Trine Maxel Juul; Susanne Eriksen Boonen; Katja Venborg Pedersen; Caroline Hey Bækgaard; Martin Larsen; Maria Kibæk; Niels Illum; Malene Heideman; Christiane Nielsen; Emilie Boye Lester; Christina Fagerberg (Clinical Genetics, 2026)
ABSTRACT Pathogenic variants on the paternal allele of IGF2 are linked to Silver–Russell syndrome (SRS). This report describes two unrelated individuals—a 5‐year‐old girl and an adult female—with de novo IGF2 missense variants, both diagnosed with SRS. While one exhibited normal development, the other had intellectual disability, highlighting phenotypic variability. A review of 20 individuals with IGF2 variants revealed that SRS features, as defined by the Netchine‐Harbison Clinical Scoring System, were most common. Additional recurrent traits included delayed speech and motor development, under‐masculinized male genitalia, hand/foot anomalies, and congenital heart defects. Growth faltering patterns varied, and intellectual disability was seen in some. We also demonstrated that long‐read sequencing can determine the allelic origin of de novo IGF2 variants using differentially methylated regions, eliminating the need for parental samples. This approach confirms long‐read sequencing as a powerful tool for identifying de novo variant origins in imprinted genes like IGF2 .